Research retrospective on the ecological state of Borzhava river basin (Transcarpathian region) - M. O. Vovkunovych (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
The Borzhava River is an important element of the region's river network and a valuable natural resource for the local population of the Zakarpattia region.